Effects of Board Processes on Board Roles Performance among Selected Savings and Credit Cooperative Societies in Tanzania - Mlay, Lilian S.; Temu, Sylvia S.; Mataba, Lucas D. (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2023)
This paper examines the effect of board processes on efforts norms, cognitive conflict, and use of skills and knowledge on the board’s performance in monitoring, resource provision and strategic roles in SACCOS in Tanzania. The social exchange theory provided theoretical guidance. A cross-sectional design with a mixed-methods approach was used. Data were collected using a questionnaire administered to 198 board chairpersons and an interview with nine key informants from SACCOS managers and cooperative officers. Data were analysed through multiple linear regression and thematic analysis. The results revealed a strong and significant relationship between effort norms and board roles’ performance in monitoring, resource provision, and strategic roles. The results further indicated a positive and significant relationship between the application of skills and the knowledge of board members, coupled with their ability to monitor and provide the board with essential resources. The results further revealed that cognitive conflict negatively influenced board members’ ability to play strategic roles. Moreover, no significant relationship was found out between cognitive conflict and board roles in monitoring or resource provision. Effort norms and the Use of board members’ skills and knowledge significantly predicted board role performance. Therefore, the study recommends that the board chairperson encourage a participatory culture to ensure that board members exert enough effort into and apply their skills and knowledge in fulfilling their roles. Furthermore[1], SACCOS members should elect board members based on their skills, knowledge, and ability to work and collaborate constructively and respectfully with other members